2018
DOI: 10.1016/j.jcot.2017.09.017
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, management and outcome assessment of post operative infection following single bundle and double bundle acl reconstruction

Abstract: Incidence of infection is higher with the double bundle technique, however, the functional outcome is not affected (p value 0.231). Joint aspirate is the gold standard diagnostic test for infection. CRP and ESR are the next dependable tests with high sensitivity but their specificity is low. A thorough debridement is necessary apart from recommended antibiotic cover of 2 weeks IV followed by 4 weeks oral antibiotics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…Of the 20 European studies reporting on 156,597 ACLRs, the average incidence of infection was 0.53% (range 0.25-1.85%) 7, 13, 15, 18-20, 26, 29, 30, 33, 34, 37, 42, 46-52 . For five studies from Asia reporting on 37,696 ACLRs, the calculated incidence of infection was 0.93% (range 0.52-1.48%) 27,32,36,40,53 . Among the 19 studies from the United States, which reported on 158,429 ACLRs, the incidence of infection was 0.54% (range 0.15-2.44%) 4, 8-11, 16, 17, 21, 23-25, 31, 35, 38, 39, 44, 45, 54, 55 .…”
Section: Resultsmentioning
confidence: 99%
“…Of the 20 European studies reporting on 156,597 ACLRs, the average incidence of infection was 0.53% (range 0.25-1.85%) 7, 13, 15, 18-20, 26, 29, 30, 33, 34, 37, 42, 46-52 . For five studies from Asia reporting on 37,696 ACLRs, the calculated incidence of infection was 0.93% (range 0.52-1.48%) 27,32,36,40,53 . Among the 19 studies from the United States, which reported on 158,429 ACLRs, the incidence of infection was 0.54% (range 0.15-2.44%) 4, 8-11, 16, 17, 21, 23-25, 31, 35, 38, 39, 44, 45, 54, 55 .…”
Section: Resultsmentioning
confidence: 99%
“…This concept is supported by a current meta-analysis that showed that the objective International Knee Documentation Committee (IKDC) score was significantly better for anatomical ACL reconstructions than for nonanatomical reconstructions [17] and by a systematic review which proved that the osteoarthritis rates after anatomical ACL reconstruction were significantly lower than after nonanatomical ACL reconstruction [18]. However, the double-bundle technique-as a special anatomical reconstruction technique-is not recommended as a standard technique due to the lack of superiority in the long term and the increased risk of complications [19][20][21].…”
Section: Discussionmentioning
confidence: 99%
“…Visualising the tunnel position is easier on the tibial side than on the femur, but incorrect positioning of the tunnel also occurs on the tibial side. Therefore, using landmarks is also recommended for tibial tunnel positioning (statements [20][21][22]. Various studies have shown that the anterior horn of the lateral meniscus is a suitable landmark for finding the centre of the tibial insertion; however, the anterior horn of the lateral meniscus does not always indicate the centre of the tibial insertion [25,28,29].…”
Section: Discussionmentioning
confidence: 99%
“…Manandhar et al 6 reported no clinical differences regarding the range of motion and functional results between early and delayed ACL reconstruction. Mohindra et al 7 found a higher incidence of infection following double-bundle ACL reconstruction, compared to a single-bundle technique.…”
Section: Editorialmentioning
confidence: 99%